Morning vs. evening: the role of exercise timing in enhancing fat oxidation in young men - Lan, H.; Wu, K.; Deng, C.; Wang, S. (Frontiers in Physiology, 2025)
Objective: This study aimed to investigate the acute effects of exercise timing (morning vs. evening) on fat oxidation and energy expenditure in young men, with a focus on interactions between exercise and meal timing.